2020
DOI: 10.3390/rs12152436
|View full text |Cite
|
Sign up to set email alerts
|

Using Satellite Thermal-Based Evapotranspiration Time Series for Defining Management Zones and Spatial Association to Local Attributes in a Vineyard

Abstract: A well-planned irrigation management strategy is crucial for successful wine grape production and is highly dependent on accurate assessments of water stress. Precision irrigation practices may benefit from the quantification of within-field spatial variability and temporal patterns of evapotranspiration (ET). A spatiotemporal modeling framework is proposed to delineate the vineyard into homogeneous areas (i.e., management zones) according to their ET patterns. The dataset for this study relied on ET retrieval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…This approach showed high prediction accuracy and revealed that the area of the vineyard planted on top of a silt loam soil had better conditions to consume more water. These findings allowed the spatial quantification of evapotranspiration time series at different temporal scales and may benefit within-season decision-making regarding the amounts, timing, and location of irrigation [256].…”
Section: Remote Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach showed high prediction accuracy and revealed that the area of the vineyard planted on top of a silt loam soil had better conditions to consume more water. These findings allowed the spatial quantification of evapotranspiration time series at different temporal scales and may benefit within-season decision-making regarding the amounts, timing, and location of irrigation [256].…”
Section: Remote Sensingmentioning
confidence: 99%
“…Indeed, precision water management in vineyards may benefit from the quantification of within-field spatial variability and temporal patterns of grapevine transpiration [256]. In this sense, a combination of time-series decomposition of evapotranspiration retrievals from multiple satellite platforms and a random forest classification algorithm has been tested in a Pinot noir vineyard in California [256]. This approach showed high prediction accuracy and revealed that the area of the vineyard planted on top of a silt loam soil had better conditions to consume more water.…”
Section: Remote Sensingmentioning
confidence: 99%
“…Within-season measurements in each of the MZs allowed investigation of MZ vine vigor and water status dynamics and its effects on yield and wine parameters. Management zones can be static, with no change of their boundaries throughout the season [14,28] or dynamic, with a change of size or class number [42,50,51]. Since our main objective in this study was to delineate MZs for…”
Section: Discussionmentioning
confidence: 99%
“…Topographic wetness index (TWI), a steady-state hydrologic variable, mainly determined by slope, can be a good parameter for IMZ as it provides an estimate of the water drainage dynamics within the field during the winter and thus affects vine water availability during the spring and summer [12]. In recent studies, TWI was used for flood risk assessment [13] and as an additional variable for IMZ delineation in vineyards [9,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation